Pengelolaan Program Edukasi Berbasis Komunitas untuk Pencegahan Bullying dan Penyebaran Hoaks: Perspektif Manajemen dan Politik di SMPN 5 Cibadak - Khozin Bakti; Try Adhi Bangsawan; M. Elang Adriansyah; Rebion Raga Munggaran; Rico Sandi Aji; Amelinda Kusbandiah W (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
This community-based education program at SMPN 5 Cibadak aims to prevent bullying and the spread of hoaxes among students through an approach that integrates management and political perspectives. The program is designed to increase students' awareness of the negative impacts of bullying and hoaxes, as well as to strengthen their active participation in maintaining a safe and informative school environment. Through a series of socialization and training, the program engages a wide range of stakeholders, including teachers, students, and parents, to build collective awareness and social responsibility. The results of this program show a significant improvement in students' understanding of the dangers of bullying and hoaxes as well as their ability to identify and report such incidents. The implementation of this program also shows the importance of participatory management in the management of educational programs, where the involvement of all parties is the key to success. The political approach in this program also helps to strengthen support from the school and the surrounding community. Overall, this program makes a positive contribution to creating a safer and more harmonious school environment, and can be used as a model to be applied in other schools.